Flavor-violating Higgs and Z boson decays at a future circular lepton collider - Kamenik, Jernej F. (2024)
Recent advances in b, c, and s quark tagging coupled with novel statistical analysis techniques will allow future high energy and high statistics electron-positron colliders, such as the FCC-ee, to place phenomenologically relevant bounds on flavor violating Higgs and Z decays to quarks. We assess the FCC-ee reach for Z/h→bs,cu decays as a function of jet tagging performance. We also update the standard model (SM) predictions for the corresponding branching ratios, as well as the indirect constraints on the flavor violating Higgs and Z couplings to quarks. Using the type III two Higgs doublet model as an example of beyond the standard model physics, we show that the searches for h→bs,cu decays at FCC-ee can probe new parameter space not excluded by indirect searches. We also reinterpret the FCC-ee reach for Z→bs,cu in terms of the constraints on models with vectorlike quarks.